Kajian Yuridis Pembuktian Berdasarkan Alat Bukti Petunjuk dalam Perkara Penipuan - Fajar Nugrahadi (Verstek, 2019)
This research aimed to investigate the suitability of cassation petition proposed by the Prosecutors based on Judex Facti ignoring the proofng tools towards the enforcement that was detached from any prosecutions in law of fraud with the Article 253 of KUHAP. This research used the normative law research method. The material sources used the primary legal material and secondary legal material. The analyzing law sources used the syllogism method and used the deductive interpretation.     The cassation petition proposed by the Prosecutors towards the enforcement that was detached from any prosecutions based on Judex Facti misapplied the law in fraud cases with the provisions contained in Article 253 verse (1) of KUHAP. Judex Facti in this case was the Airmadidi District Court in making enforcement did not apply the proper law and they not judging in accordance with the provisions of the law because they ignored the judicial evidence that was in accordance with the Article 184 of KUHAP (witness testimony, experts testimony, defendant testimony, document evidence and judicial evidence).Keywords: Cassation, Prosecutors, The Court Enforcement, Fraud